2016
DOI: 10.1002/ps.4362
|View full text |Cite
|
Sign up to set email alerts
|

Costs and benefits of insecticide and foliar nutrient applications to huanglongbing‐infected citrus trees

Abstract: All treatments resulted in production and financial gains relative to controls. However, material and application costs associated with the nutrition component offset these gains, resulting in lesser benefits than insecticides applied alone. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 34 publications
1
55
0
Order By: Relevance
“…• Poncirus trifoliata L., rootstock. Planting density was 373 trees • ha -1 (151 trees • ac -1 ) at 7.3 m between rows and 3.7 m within rows (Stansly et al, 2014;Tansey et al, 2016). Trees were irrigated with undertree, microsprinklers, and standard weed control and fertilization practices were followed (Davies and Jackson, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Poncirus trifoliata L., rootstock. Planting density was 373 trees • ha -1 (151 trees • ac -1 ) at 7.3 m between rows and 3.7 m within rows (Stansly et al, 2014;Tansey et al, 2016). Trees were irrigated with undertree, microsprinklers, and standard weed control and fertilization practices were followed (Davies and Jackson, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Many growers are coping with HLB by controlling the psyllid vector (Stansly et al, 2010(Stansly et al, , 2014Tansey et al, 2016) with insecticides and managing tree disease symptoms with foliar nutrient sprays (Giles, 2011;Tansey et al, 2016). Foliar applications deliver micronutrients to counteract HLBinduced deficiencies (Masuoka et al, 2011), salts of phosphorus acid to aid in nutrient assimilation and compounds such as salicylic acid, that are thought to activate systemic acquired resistance pathways (SAR) in the tree.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have demonstrated that productivity of infected trees can be maintained at sustainable levels, at least in the short term, when specific agronomic measures are taken. Among them, preventing new bacterial re‐inoculations through the suppression of infective vectors can drastically reduce the rapid decline of the tree and extent its productivity . Hence, effective action against this disease, whether it is present or not, can be achieved through efficient vector management.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, preventing new bacterial re-inoculations through the suppression of infective vectors can drastically reduce the rapid decline of the tree and extent its productivity. 21,22 Hence, effective action against this disease, whether it is present or not, can be achieved through efficient vector management. Current vector management programs rely on frequent insecticide applications aimed to keep ACP numbers as close to zero as possible.…”
Section: Introductionmentioning
confidence: 99%